Effect of metformin monotherapy on cardiovascular diseases and mortality: a retrospective cohort study on Chinese type 2 diabetes mellitus patients. Issue 1 (December 2015) - Fung, Colman; Wan, Eric; Wong, Carlos; Jiao, Fangfang; Chan, Anca
Abstract Background Many factors influence whether the first-line oral anti-diabetic drug, metformin, should be initiated to a patient with type 2 diabetes mellitus (T2DM) early in the course of management in addition to lifestyle modifications. This study aims to evaluate the net effects of metformin monotherapy (MM) on the all-cause mortality and cardiovascular disease (CVD) events. Methods A retrospective 5-year follow-up cohort study was conducted on Chinese adult patients with T2DM and without any CVD history under public primary care. Cox proportional hazard regressions were performed to compare the risk of all-cause mortality and CVD events (CHD, stroke, heart failure) between patients receiving lifestyle modifications plus MM (MM groups) and those with lifestyle modifications alone (control groups). Results 3400 pairs of matched patients were compared. MM group had an incidence rate of 7.5 deaths and 11.3 CVD events per 1000 person-years during a median follow-up period of 62.5 months whereas control group had 11.1 deaths and 16.3 per 1000 person-years during a median follow-up period of 43.5–44.5 months. MM group showed a 29.5 and 30–35 % risk reduction of all-cause mortality and CVD events (except heart failure) than control group (P < 0.001). MM group was more prone to progress to chronic kidney disease but this was not statistically significant. Conclusions Type 2 diabetic patients who were started on metformin monotherapy showed improvement in many of the clinical parameters and a reduction in all-cause mortality and CVD events than lifestyle modifications alone. If there is no contraindication and if tolerated, diabetic patients should be prescribed with metformin early in the course of the diabetic management to minimize their risk of having the cardiovascular events and mortality in the long run.